Fully weekly antituberculosis regimen: a proof-of-concept study. Issue 3 (3rd September 2020) - Kort, Fatma; Fournier Le Ray, Laure; Chauffour, Aurélie; Jarlier, Vincent; Lounis, Nacer; Andries, Koen; Aubry, Alexandra; Guglielmetti, Lorenzo; Veziris, Nicolas
Background: The World Health Organization recommends supervising the treatment of tuberculosis. Intermittent regimens have the potential to simplify the supervision and improve compliance. Our objective was to analyse the sterilising activity of once-weekly regimens based on drugs with a long half-life, bedaquiline and rifapentine, in a murine model of tuberculosis. Methods: 300 Swiss mice were infected intravenously infected with ×10 −6  CFU Mycobacterium tuberculosis H37Rv. Mice were treated once weekly with regimens containing: 1) bedaquiline, rifapentine and pyrazinamide (BPZ); 2) BPZ plus moxifloxacin (BPZM); 3) BPZM plus clofazimine (BPZMC); 4) the standard daily regimen of tuberculosis. All regimens were given for 4 or 6 months. Bactericidal and sterilising activity were assessed. Results: After 2 months of treatment, the mean count in lungs was 0.76±0.60 log10 CFU in mice treated with the daily control regimen and negative in all mice treated with once-weekly regimens (p<0.05 compared to the daily control). All mice had negative lung cultures on completion of either 4 or 6 months of treatment, whereas 3 months after 4 and 6 months of treatment, respectively, the relapse rate was 64% and 13% in the standard daily regimen, 5% and 0% in BPZ, 0% and 0% in BPMZ and 0% and 5% in BPMZC (p<0.05 for all once-weekly regimens versus 4-month daily control; p>0.05 for all once-weekly regimens versus 6-month daily control). Conclusions: BPZ-based once-weekly regimens have higher sterilising activity than the standard daily regimen and could greatly simplify treatment administration and possibly shorten the duration of tuberculosis treatment. Bedaquiline–rifapentine–pyrazinamide-based once-weekly regimens have higher sterilising activity than the standard daily regimen of tuberculosis and could thus greatly simplify treatment of tuberculosis https://bit.ly/2W8yx2r